Corrections to “Toward Privacy Preservation Using Clustering Based Anonymization: Recent Advances and Future Research Outlook” - Abdul Majeed; Safiullah Khan; Seong Oun Hwang (IEEE Access)
Presents corrections to the paper, Corrections to “Toward Privacy Preservation Using Clustering Based Anonymization: Recent Advances and Future Research Outlook”.